Prevalence and risk factors of low back pain and disability index among operating room nurses - Anita Jeyakumar; Florence Segaran (Journal of Perioperative Nursing)
Low Back Pain (LBP) is one of the most common complaints requiring medical attention and is the most common form of musculoskeletal disorder. It is estimated that over half of the general population will seek medical care for back pain at some point in their lives. Globally, the prevalence of LBP among the general population ranges between 15 and 45 per cent.